Tracking brucellosis–a re-emerging disease. Issue 1 (October 2021) - Schaeffer, J; Revilla-Fernández, S; Hofer, E; Djordjevic, V; Lakicevic, B; Indra, A; Schmoll, F; Allerberger, F; Ruppitsch, W
Abstract: Brucellosis caused by members of the genus Brucella is of major concern for animal and public health and is recognized as a re-emerging zoonotic disease. Brucellosis causes flu-like symptoms like fever, sweats, weakness, pain in muscles, joint and back, with some symptoms persisting for longer time periods. Infections occur through consumption of unpasteurized dairy products or undercooked meat, inhalation, and contact with animals. Human-to-human transmission is rare. Surveillance of this disease in animals and humans and prevention of infection risks factors are the most effective strategies to prevent brucellosis. With the progress in sequencing technologies, whole genome sequencing (WGS) has become an effective tool in surveillance, tracking of pathogens and in outbreak investigation. WGS allows identification of the source of infection and to elucidation of transmission chains, which enables authorities to implement timely and appropriate interventions.